Prostate-specific antigen screening in elderly men. (April 2011) - Leavitt, David A; Konety, Badrinath R
Prostate cancer is the most common noncutaneous cancer in men, it predominantly afflicts elderly men and it will assume increasing importance as the population at large ages. Prostate cancer is variable in its behavior and represents a spectrum of aggressiveness. Prostate cancer screening with prostate-specific antigen (PSA) was first introduced in the early 1980s. Since its introduction, PSA has become not only the most commonly used biomarker for cancer screening, but also the most contentious. Robust, randomized studies elucidating the unequivocal benefits of PSA screening are lacking. The void of reliable evidence has created a confusing environment surrounding the potential advantages, disadvantages, overdiagnosis and overtreatment associated with PSA screening. Current recommendations from leading medical organizations disagree on the appropriateness of PSA screening in all men, especially elderly men; however, there appears to be a trend toward shared decision-making between patient and physician that incorporates patient-specific comorbidities and overall health.